Total factor productivity growth of the crop sector in Kerala - N. Karunakaran
Productivity growth in agriculture is both a necessary and sufficient condition for its development. Total factor productivity (TFP) is an important measure to evaluate the performance of any production system and sustainability of a growth process. There are several reports that total factor productivity growth is declining over the years in many parts of India even with the application of increased inorganic fertilisers. The cropping system is sustainable if it can maintain total factor productivity growth over time. The TFP growth rate showed stagnation in the crop sector (negative and very low TFP growth rate Annum -1 ) in Kerala and a similar pattern was observed in all districts. A perspective of the TFP changes across the districts and state and the percentage share of total factor productivity in output growth of the crop sector in Kerala showed clear signs of unsustainability of the crop sector. The study revealed that all the districts (except Kollam, Idukki, Wayanad and Palakkad) and the state as a whole, the share of TFP in the output growth was negative during the time period 1980-81 to 2009-10. The period wise analysis also derived deceleration in the total factor productivity growth.